Evolution of genetic markers for drug resistance after the introduction of dihydroartemisinin–piperaquine as first-line anti-malarial treatment for uncomplicated falciparum malaria in Indonesia - Rahmasari, FV; Asih, PBS; Rozi, IE; Wangsamuda, S; Risandi, R; Dewayanti, FK; Permana, DH; Syahrani, L; Prameswari, HD; Basri, HH; Bustos, MDG; Charunwatthana, P; et al. (BioMed Central, 2023)
Background Dihydroartemisinin–piperaquine has been Indonesia’s first-line anti-malarial treatment since 2008. Annual therapeutic efficacy studies (TES) done in the last 12 years showed continued high treatment efficacy in uncomplicated Plasmodium falciparum malaria. Although these studies did not show evidence for artemisinin resistance, a slight increase in Late Treatment Failure was observed over time. It is highlight to explore the evolution of genetic markers for ACT partner drug resistance since adopting DHA–PPQ. Methods Dry blood spots were identified from a mass blood survey of uncomplicated falciparum malaria patients (N = 50) in Sumba from 2010 to 2018. Analysis of genotypic profile (N = 51) and a Therapeutic Efficacy Study (TES) from Papua (N = 142) from 2020 to 2021, 42-day follow-up. PCR correction using msp1, msp2, and glurp was used to distinguish recrudescence and reinfection. Parasite DNA from DBSs was used for genotyping molecular markers for antimalaria drug resistance, including in Pfk13, pfcrt, and pfmdr1, as well as gene copy number variation in pfpm2/3 and pfmdr1. Results The study revealed the absence of SNPs associated with ART resistance and several novel SNPs such as L396F, I526V, M579I and N537S (4.25%). In Sumba, the mutant haplotype SDD of pfmdr1 was found in one-third of the isolates, while only 8.9% in Papua. None of the pfcrt mutations linked to piperaquine resistance were observed, but 71% of isolates had pfcrt I356L. Amplification of the pfpm2/3 genes was in Sumba (17.02%) and Papua (13.7%), while pfmdr1 copy number prevalence was low (3.8%) in both areas. For the TES study, ten recurrences of infection were observed on days 28, 35, and 42. Late parasitological failure (LPF) was observed in 10/117 (8.5%) subjects by microscopy. PCR correction revealed that all nine cases were re-infections and one was confirmed as recrudescence. Conclusion This study revealed that DHA–PPQ is still highly effective against P. falciparum. The genetic architecture of the parasite P. falciparum isolates during 2010–2021 revealed single copy of Pfpm2 and pfmdr1 were highly prevalent. The slight increase in DHA–PPQ LTF alerts researchers to start testing other ACTs as alternatives to DHA–PPQ for baseline data in order to get a chance of achieving malaria elimination wants by 2030.